Business Ecosystem Development in Corporate Business Strategy - Noviyanti , Noviyanti; Tricahyono, Dodie (Jurnal Bisnis dan Pemasaran Digital, 2024)
Purpose: The objective of this research is to identify the parties involved in the agro-business ecosystem in Kabupaten Bandung and determine the factors influencing the development of strategies at PT BANDUNG DAYA SENTOSA as a Regional Government-Owned Enterprise (BUMD) operating in the Agribusiness sector. Research methodology: This study uses a business ecosystem approach to map the roles and parties involved in the agro-business ecosystem in Kabupaten Bandung. This study employed a qualitative research method with a case study design. Results: Through multi-agent-based ecosystem modeling and business model reconfiguration, it can be concluded that adaptability and collaboration among actors in the agribusiness ecosystem in Kabupaten Bandung are key to success. The Regional Government-Owned Enterprise Bandung Daya Sentosa (BDS) has the potential to become an innovation hub and enhance its role through the development of innovative agricultural products and utilization of digital technology. Conclusions: PT Bandung Daya Sentosa (BDS) has demonstrated strong potential to lead national agribusiness innovation by leveraging digital platforms like BDSMart and implementing multi-actor ecosystem strategies. Collaboration and adaptability among stakeholders are key to driving sustainable growth in the Bandung Regency agricultural sector. Through strategic use of technology and stakeholder engagement, BDS strengthens its role as a connector, innovator, and enabler in the agribusiness ecosystem. Limitations: This study is context-specific to the agribusiness ecosystem in Bandung Regency, and its findings may not be directly transferable to other regions with different economic, cultural, or policy environments. Contributions: PT Bandung Daya Sentosa acts as a key integrator and innovator in the agribusiness ecosystem, fostering collaboration among stakeholders. Farmers contribute as primary producers, supported by training, finance, and technology. Academics, government, media, and logistics providers each play vital roles in enabling innovation, governance, market reach, and the smooth distribution of goods, collectively enhancing ecosystem resilience and sustainability.